CARA EFEKTIF MENYUSUN KARYA TULIS YANG SISTEMATIS BAGI MAHASISWA KESEHATAN - Masyfufah, Lilis; Sutha, Diah Wijayanti (Abdi Panca Marga, 2024)
Writing scientific papers is still an obligation for university student to graduate from their education, including heath students. In the health department, the written work prepared is problem solving. One of the courses that must be taken to support this final assignment is Methodology of Health Science, but it is still felt not enough to make a students understand to produce a systematic final work. Therefore, need a training about “The Effective Ways to Prepare Systematic Writing for Health Collages. The activity method is carried out by means of online training, with the aim of covering more participants and can be accessed from anywhere. The result of this activity is that participants are given exposure regarding how to check written work so that it systematically complies with the rules for writing scientific papers. Written work for a final project majoring in health must start from a problem which is the studied using certain theories and methods, so that it can produce a relevant solution to the problem. This activity took place with active participants because it was to be given especially to final yeat health student. Keywords: research method, scientific writing training, scientific paper for health student References Ilfiandra, Ilfiandra et al. 2016. “Pelatihan Dan Pendampingan Penulisan Karya Tulis Ilmiah Untuk Guru Di Indonesia.” Jurnal Pengabdian Pada Masyarakat 1(1): 70–80. Jumono, Sapto, Sri Handayani, Abdurrahman Abdurrahman, and Chajar Matari Fath Mala. 2021. “Pelatihan Penyusunan Artikel Publikasi Pada Mahasiswa Perguruan Tinggi Di Jakarta.” Prosiding Hasil Pengabdian Masyarakat: 130–34. Masturoh, Imas, and Nauri Anggita. 2018. Pusat Pendidikan Sumber Daya Manusia Kesehatan Badan Pengembangan dan Pemberdayaan Sumber Daya Manusia Kesehatan Metodologi Penelitian Kesehatan. Edisi Tahu. Jakarta: Kementerian Kesehatan RI. Prodi D3 Rekam Meids dan Informasi Kesehatan. 2022. Buku Panduan KTI. Surabaya: STIKES Yayasan RS Dr. Soetomo. Ilfiandra, Ilfiandra et al. 2016. “Pelatihan Dan Pendampingan Penulisan Karya Tulis Ilmiah Untuk Guru Di Indonesia.” Jurnal Pengabdian Pada Masyarakat 1(1): 70–80. Jumono, Sapto, Sri Handayani, Abdurrahman Abdurrahman, and Chajar Matari Fath Mala. 2021. “Pelatihan Penyusunan Artikel Publikasi Pada Mahasiswa Perguruan Tinggi Di Jakarta.” Prosiding Hasil Pengabdian Masyarakat: 130–34. Masturoh, Imas, and Nauri Anggita. 2018. Pusat Pendidikan Sumber Daya Manusia Kesehatan Badan Pengembangan dan Pemberdayaan Sumber Daya Manusia Kesehatan Metodologi Penelitian Kesehatan. Edisi Tahu. Jakarta: Kementerian Kesehatan RI. Prodi D3 Rekam Meids dan Informasi Kesehatan. 2022. Buku Panduan KTI. Surabaya: STIKES Yayasan RS Dr. Soetomo. Ratna, Ratna, Dias Andris, Entika Fani Prastikawati, and Ajeng Setyorini. 2009. “Pelatihan Penulisan Artikel Ilmiah Guru Bahasa Inggris SMA Di Kota Semarang (Sebagai Pencapaian KEPMENPAN Nomor 16 Tahun 2009 Tentang Jabatan Fungsional Guru Dan Angka Kreditnya).” Jurnal Pengabdian Pada Masyarakat 2(5): 255. Saman, Abdul, and Muhammad Ilham Bakhtiar. 2018. “Karya Tulis Ilmiah Bagi Mahasiswa Stkip Andi Matappa Kabupaten Pangkep.” Jurnal Terapan Abdimas 3(1): 39. Swari, Utami Ratna. 2020. “Pelatihan Menulis ‘Descriptive Text’ Di Kelurahan Manguharjo Kecamatan Mayangan Kota Probolinggo.” 1(1): 14–19. Taylor, Steven J., Robert Bogdan, and Marjorie L. DeVault. 2016. Introduction to Qualitative Research Methods: A Guidebook and Resource. 4th Editio.